Jornalismo imersivo: o uso da realidade virtual e dos vídeos em 360° na produção da reportagem Baía 360º da agência pública - Felizardo, Alice Kilppe (2023)
This study investigates the impact of the use of Virtual Reality (VR) through 360° videos in journalism, focusing on Agência Publica’s series Baía 360°, which addresses the problem of pollution in Guanabara Bay, in Rio de Janeiro (RJ). The research will adopt documentary analysis methods to highlight the contributions of these technologies, integrating the results with a bibliographic survey on the subject. The central objective is to identify the contributions and challenges of VR in the construction of immersive journalism, highlighting how the technology can bring viewers closer to the events being reported. Despite the technical and financial challenges associated with producing content in these formats, the growing availability of VR devices and 360° video platforms expands their potential. The study emphasizes the importance of innovation and experimentation in constantly evolving journalism, promoting an engaging and interactive news narrative. Finally, this research seeks to contribute to an understanding of the benefits and challenges of integrating virtual reality and 360° videos into journalism, encouraging their adoption and improvement.